Strategi Promosi di Perpustakaan STIQSI (Sekolah Tinggi Ilmu Al-Qur’an Dan Sains Al-Ishlah) - Moh Azharul Kholili; Wahyu Harianto; Nita Mudawamah (UIN Maulana Malik Ibrahim Malang, 2023)
The promotion aims to introduce and disseminate the products and services available at the library to increase user interest and increase the utilization and utilization of the library in enhancing the reading culture of its users. In this study, the strategic management method and the output of this research was the formulation of a suitable library promotion strategy to be implemented in the STIQSI library. In addition, SWOT analysis is also used, namely the identification of various factors systematically to formulate a library strategy. This analysis is based on logic that can maximize strengths and opportunities while minimizing weaknesses and threats. The subjects in the study were STIQSI librarians who knew extensively about the internal and external factors of the STIQSI library. At the same time, the object of this research is a library promotion strategy using strategic management methods, including two stages: environmental analysis and strategy formulation. This research uses a descriptive qualitative approach because this research will describe the formulation of the STIQSI library promotion strategy. The researcher collect data according to conditions in the field without manipulating the data obtained. This research found that the STIQSI Library still requires various efforts to promote the library. It is intended to increase interest in reading and visiting the library. Some forms of promotion that the STIQSI Library can carry out are: creating social media and websites, procuring activities such as training in information retrieval skills, procuring library holiday commemorations, providing scientific and popular writing training, and training on accessing journals and journal databases. It is hoped that these activities can help the STIQSI Library in terms of promoting a better libraryKeywords: Library Promotion, Strategic Management, SWOT Analysis